A first-order kinetic model for designing anaerobic ponds in the treatment of palm oil mill effluent - Wong, K. K.; Springer, A. M. (Applied Science Publishers, 1981)
Anaerobic ponds have been used as an initial step in the treatment of palm oil mill effluent (POME). Data on BOD loading rate and subsequent reduction exist but no systematic attempts have been made to synthesise these data into a theoretical framework for proper engineering design. This paper discusses alternative kinetic models for the design of ponding systems. First-order kinetic rate coefficients, k, are derived from the analysis of existing data from several sources. The average k value was found to be 0·36 day-I. With this theoretical model, derived from practical data, a simple approach can be used to arrive at an effective design. A case for further aerobic waste treatment following the anaerobic ponds is proposed.